Different Effectiveness of Prenatal Gymnastics and Prenatal Yoga in Back Pain to The Third Trimester Pregnant Women In Working Area of Puskesmas Kendalsari and Clinical Midwifery Practice Yulis Indriana. - Finisia, Hirdanti; Rahayu, Sri; Triningsih, Reni Wahyu (Ikatan Bidan Indonesia (IBI), 2024)
Abstract: Back pain is a physiological discomfort which pregnant woman in third trimester often experience. Light sport such as prenatal gymnastis and prenatal yoga are two among several of back pain non-pharmacological management. This sudy aims to analyze the reduction differences of low back pain in the third trimester of pregnant woman between those given prenatal gymnastic and prenatal yoga. This is a quasi experimental study, each group performed pretest and posttest. The population is 40 people and sample amounted to 32 respondents, 16 respondents to prenatal gymnastic and 16 respondents to prenatal yoga, by pusposive sampling technique. Instrument for pain measure is Numeric Rating Scale (NRS) pain scale. The result of this study that decrease back pain occurs on the prenatal yoga is 16 respondent (100%) experienced mild pain in the 1-3 pain scale. Data were being analyzed by Paired Sample T-test probability values obtained (p) 0,000 smaller then 0,05 (p<0,05). While the result of data analyzed by Independent Sample T-test probability values (p result is that both prenatal gymnastic and prenatal yoga contribute lower pain, but prenatal yoga perform greater influence at reducing of back pain in pregnant woman. Keywords: prenatal gymnastic, prenatal yoga, back pain in third trimester pregnancy.